ChemInform Abstract: A Novel Domino Condensation—Intramolecular Nucleophilic Cyclization Approach Towards Annulated Thiochromenes. Issue 3 (21st January 2014) - Voskressensky, Leonid G.; Sokolova, Ekaterina A.; Festa, Alexey A.; Varlamov, Alexey V.
Abstract A domino reaction of isoquinoline‐derived iminium salts and α‐mercapto benzaldehydes provides access to previously unknown annulated thiochromenes.